1978
DOI: 10.1042/bj1730263
|View full text |Cite
|
Sign up to set email alerts
|

Inaccuracies in measurement of conjugated and unconjugated bilirubin in bile with ethyl anthranilate diazo and solvent-partition methods

Abstract: A criticial evaluation was made of the ethyl anthranilate diazo and two solvent-partition methods for the determination of conjugated and unconjugated bilirubin in human and rat bile. The ethyl anthranilate diazo reagent, which reacts only with conjugated bilirubin in serum, also diazotized a variable proportion of unconjugated bilirubin in bile and thus overestimated the concentration of monoconjugates. With the Weber-Schalm and modified Folsch solvent-partition methods applied to human or rat bile, 4--9% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…It is essential to buffer the sample first to pH 2.7 before adding the diazo-reagent, because otherwise the reaction mixture may temporarily be at pH above 3, causing diazocleavage of unconjugated bilirubin (24). Also, for bile, appropriate dilution (20-fold or more) is required because otherwise added or endogenous bilirubin may react to a considerable extent (26), probably owing to the reactionpromoting effect of bile salts. By subsequent TLC of the azopigment extracts (25), unconjugated azodipyrrole was separated from azodipyrrole glucuronide and the ratio: r = unconjugated azodipyrrole/azodipyrrole glucuronide (Eq.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to buffer the sample first to pH 2.7 before adding the diazo-reagent, because otherwise the reaction mixture may temporarily be at pH above 3, causing diazocleavage of unconjugated bilirubin (24). Also, for bile, appropriate dilution (20-fold or more) is required because otherwise added or endogenous bilirubin may react to a considerable extent (26), probably owing to the reactionpromoting effect of bile salts. By subsequent TLC of the azopigment extracts (25), unconjugated azodipyrrole was separated from azodipyrrole glucuronide and the ratio: r = unconjugated azodipyrrole/azodipyrrole glucuronide (Eq.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study a new and more sensitive procedure for quantitation of plasma bilirubin has been used, obviating the use of the Weber-Schalm solventpartition method (24) that has been widely adopted (8,22,25) despite its documented inaccuracies (8,(26)(27)(28). Using this procedure we have examined the hepatic transport kinetics of radiobilirubin in 30 intact rats and developed a compartmental model that described all experimental data obtained from plasma, liver, and bile.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it has been shown that both methods are inadequate. The solvent partition method does not separate conjugated and unconjugated bilirubin adequately and does not distinguish between the various conjugated forms of bilirubin (7,8). Although the formation of the diazonium salts has been applied successfully to both clinical and research problems for a number of years, it has become apparent that the diazo procedures directed at separating bilirubin and its conjugates have also been hampered by the participation of unconjugated bilirubin, to a small extent, in the diazo reaction under conditions initidly considered to be conducive of reaction only with the conjugated bilirubins (9).…”
mentioning
confidence: 99%